2020
DOI: 10.1080/19407963.2020.1721638
|View full text |Cite
|
Sign up to set email alerts
|

Immersive event experience and attendee motivation: a quantitative analysis using sensory, localisation, and participatory factors

Abstract: Immersive events" is a growing category within the range of event typologies that includes participatory theatre, interactive launch parties, 'escape rooms' and dress-up cinema.A conceptual model reflects three core elements of the immersive events: Interaction, Sensory experience, and Localisation. A targeted online survey obtained a sample of n = 201 participants who had attended an immersive event within the past year.The results reveal that novelty and entertainment are highly important to attendee motivat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…The addition of interactivity was only supplementary to boosting the stigma reduction effect. The results confirmed previous suggestions that enhanced motivation through perceived autonomy and immersiveness would lead to enhanced stigma reduction [ 43 , 44 ]. This study provides empirical support for the rationale behind the use of internet-based storytelling programs, especially for those with stigma-related stories and interactivity.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The addition of interactivity was only supplementary to boosting the stigma reduction effect. The results confirmed previous suggestions that enhanced motivation through perceived autonomy and immersiveness would lead to enhanced stigma reduction [ 43 , 44 ]. This study provides empirical support for the rationale behind the use of internet-based storytelling programs, especially for those with stigma-related stories and interactivity.…”
Section: Discussionsupporting
confidence: 90%
“…Research has found interactivity to have a significant role in improving information processing through enhanced motivation, which facilitates stigma reduction [ 26 ]. Perceived autonomy and immersiveness have been found to enhance motivation [ 43 , 44 ]. Thus, they might be possible mediators of the effect of interactivity although their relationships remain untapped.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, and for our case, these theories are complemented by the concept of 'design for all' or 'universal design'. And, more specifically, this idea of the domestication of technology, of adapting technology to the needs, possibilities and expectations of the consumer, in this specific case, we will also base ourselves on research on the incorporation of odors or aromas to artistic production in general and cinema in particular (Berker, Hartmann, and Punie 2005;Pett 2021;Shiner 2020;Sobitan and Vlachos 2020;Thornton 2020). This paper's primary objective is to evaluate to what extent, if any, the incorporation of scents in movie theaters can increase enjoyment of a pastime (watching movies in traditional movie theaters) that, according to all available data, is threatened by new forms of cinematographic consumption.…”
Section: Theories Of Taste and The Domestication Of Technologymentioning
confidence: 99%
“…e host and the professional conference organizer (PCOs) are the two core subjects of the convention project, among which the professional conference organizer of the convention project is the main body of the project management and operation, which is responsible for meeting the objectives and improving the satisfaction of the attendees [1]. erefore, a large number of scholars have explored the motivation of the attendees, to guide the professional conference organizers to improve the performance of the convention projects to the needs of the attendees oriented [2,3]. In contrast, the host of the convention project, as the initiator of the project, is not the direct subject to meeting the participants, but there is a principalagent relationship between the host and the professional conference organizer [4].…”
Section: Introductionmentioning
confidence: 99%